Seasonal Variation of Fungal Biodiversity in Polluted Yamuna River from NCR Delhi Region, India - Gayatri Tripathy; P. N. Chowdhry (Innovations in Microbiology and Biotechnology Vol. 4, 2022)
The River Yamuna is the Ganga’s greatest tributary. This river is as well-known and revered as the Ganga itself. Water quality degradation as a result of pollution discharged from allochthonous and autochthonous sources into water bodies is rapidly rendering natural water bodies unsuitable for numerous beneficial purposes to mankind, such as drinking water, bathing, navigation, fishing, and irrigation. It has been discovered that over-pollution of such sacred rivers promotes microbial diversity, which raises Biochemical Oxygen Demand (BOD) and organic load in the water, therefore polluting the water. A higher BOD indicates a low level of oxygen and a higher level of pathogen (microbial) content. The study found that fungal biodiversity is increasing as a result of increased pollution in the Yamuna River, and that it is also varied depending on seasonal and climatic changes.